PENTINGNYA PENDIDIKAN HUKUM UNTUK MENCEGAH BULLYING DI LINGKUNGAN SMK BANI MAHFUD SUMEDANG - Hendar, Jejen; Rohman, Abdul; Jambak, Fabian Fadhly (Pamulang university, 2024)
Bullying, a form of aggressive behavior characterized by intentional repetitive damage, has become a common problem in schools around the world. Its detrimental effects on victims' social-emotional well-being, academic achievement, and overall health have raised concerns among educators, parents, and policymakers. To effectively address these issues, it is imperative to implement preventive measures and create a safe and inclusive learning environment. This article uses normative juridical writing methods, with secondary data materials with primary data, secondary data and tertiary data, analyzed using analytical descriptive methods. Legal education has an important role in efforts to prevent bullying behavior at SMK Bani Mahfud and other schools. Through legal education, students can gain a better understanding of their rights and responsibilities as individuals. They can learn about the laws and regulations in place to protect them from bullying and how to take action if they become victims.